Ozone Loss in the Arctic Stratosphere as Observed by Match - Rex, M.; von der Gathen, P.; Schulz, A.; Steger, J.; Gernandt, H.; Harris, N.; Reimen, E.; Bech, A.; Alfier, A.; Chippertield, M.; Kilbane-Dawe, I.; Allart, M.; et al. (2004)
We present box model calculations of ozone loss rates corresponding to the results of the Match experiment 1991/92.